Роль изучения протеиназ-ингибиторной системы в определении тактики лечения при доброкачественных узловых образованиях молочной железы - Усманова, Т.Э. (Таврический медико-биологический вестник, 2012)
Проведено обстеження 35 пацієнток з доброякісними вузловими утвореннями молочної залози. Клінічні групи хворих: одна група – с доброякісними вузловими утвореннями молочної залози без ознак запалення; друга група – із запальними змінами. Контрольна група – 12 жінок без патології молочних залоз. У доброякісних вузлових утвореннях молочної залози з ознаками запалення на місцевому рівні спостерігається зростання протєїназ і дефіцит кислотостабільних інгібіторів, що обгрунтовує вживання адекватної протизапальної терапії для запобігання прогресу, ризику малігнізації та рецидивів патології. Thirty-five women with benign nodular formations in mammary glands have been examined. There were two clinical groups of patients: in one of them, the patients had benign nodular formations of the mammary gland without the signs of inflammation; the other group consisted of patients with benign nodular formations of mammary glands with inflammatory complications. The control group consisted of 12 women without pathology of mammary glands. In benign nodular formations of mammary glands with the signs of inflammation at the local level a proteinase growth and a deficit of acid-stable inhibitors were observed, which validates a corresponding anti-inflammatory therapy for prevention of progress, risk of malignization or relapses of the pathology.